2009
DOI: 10.1007/s10735-009-9244-z
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation dependent expression of urocortin’s mRNA and peptide in human osteoprogenitor cells: influence of BMP-2, TGF-beta-1 and dexamethasone

Abstract: Urocortin-1 (UCN) a corticotropin releasing-factor (CRF) related peptide, has been found to be expressed in many different tissues like the central nervous system, the cardiovascular system, adipose tissue, and skeletal muscle. The effects of UCN are mediated via stimulation of CRF-receptors 1 and 2 (CRFR1 and 2, CRFR’s) with a high affinity for CRFR2. It has been shown that the CRF-related peptides and CRFR’s are involved in the regulation of stress-related endocrine, autonomic and behavioural responses. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
2
7
1
1
Order By: Relevance
“…Interestingly, nuclear localization was not observed in case of CRF immunoreactivity, suggesting potentially different mechanism of signal transduction thought CRF receptors. Similarly, nuclear localization of UCN1 was observed previously in human retinal pigment epithelium and differentiating human osteoprogenitor cells (Tezval et al, 2009). Furthermore, treatment of immortalized HaCaT keratinocytes with UCN1, but not CRF resulted in rapid accumulation of Ca 2þ in the nucleus (Wiesner et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, nuclear localization was not observed in case of CRF immunoreactivity, suggesting potentially different mechanism of signal transduction thought CRF receptors. Similarly, nuclear localization of UCN1 was observed previously in human retinal pigment epithelium and differentiating human osteoprogenitor cells (Tezval et al, 2009). Furthermore, treatment of immortalized HaCaT keratinocytes with UCN1, but not CRF resulted in rapid accumulation of Ca 2þ in the nucleus (Wiesner et al, 2003).…”
Section: Discussionsupporting
confidence: 79%
“…Unlike osteoclasts, we found that pre-osteoclasts expressed CRFR2b but not UCN itself. This is in contrast to a study by Tezval et al (2009), demonstrating the presence of UCN in human mesenchymal progenitor cells, but these cells had been directed toward an osteoblastic phenotype. Our findings suggest that UCN might represent an autocrine regulator of osteoclast function and a paracrine regulator of maturation and the concentration of UCN in the surrounding milieu could be controlled by osteoblastic CRF-BP release.…”
Section: Discussioncontrasting
confidence: 99%
“…3). These results were in agreement with previously published reports in terms of MSC characteristics of these trabecular bone-derived cells (Tezval et al 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Subconfluent monolayers of cells were removed with 0.25% trypsin containing 1 mM EDTA (Biological Industries Ltd., Kibbutz Beit Haemek, Israel) and serially passaged at a ratio of 1:3. Obtained MSCs were characterized on the basis of immunohistochemistry, and flow cytometry analyses and according to their differentiation potentials as reported previously (Tezval et al 2009;all described below). To characterize the MSCs, monolayer cultures were fixed with methanol and air-dried.…”
Section: Isolation Of Human Trabecular Bone-derived Mscsmentioning
confidence: 99%